2008
DOI: 10.1088/0957-4484/19/32/325705
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of polycarbonate nanotube buckypaper composite sheets

Abstract: The thermogravimetric, mechanical, and electrical properties of composite sheets produced by infiltrating single-wall carbon nanotube films (also known as 'buckypapers') with polycarbonate solution were characterized. The composite sheets showed improved stiffness and toughness, while the electrical conductivity decreased, as compared to a neat buckypaper. In addition, polycarbonate/buckypaper composite sheets showed higher resistance to handling and processing damages. Experimental results suggest the viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 29 publications
8
90
1
1
Order By: Relevance
“…Since four different film thicknesses are explored, instead of comparing the absolute resistance values, the percent change in resistance before and after epoxy infusion is calculated and tabulated in the first row of Table 1. As can be seen from the first row of Table 1, the infusion of epoxy causes the bulk resistance of the films to increase, as has also been observed by other researchers [40,41]. In particular, the increase in resistance is inversely related to film thickness; 29 bilayer films increase their resistance by an average of 148.7%, whereas the 150 bilayer sample set increases only 28.3% (Table 1).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Since four different film thicknesses are explored, instead of comparing the absolute resistance values, the percent change in resistance before and after epoxy infusion is calculated and tabulated in the first row of Table 1. As can be seen from the first row of Table 1, the infusion of epoxy causes the bulk resistance of the films to increase, as has also been observed by other researchers [40,41]. In particular, the increase in resistance is inversely related to film thickness; 29 bilayer films increase their resistance by an average of 148.7%, whereas the 150 bilayer sample set increases only 28.3% (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…In particular, the increase in resistance is inversely related to film thickness; 29 bilayer films increase their resistance by an average of 148.7%, whereas the 150 bilayer sample set increases only 28.3% (Table 1). Pham et al [40] have also reported similar findings during their study of infusing buckypapers of various thicknesses with polycarbonate.…”
Section: Resultssupporting
confidence: 53%
“…These improvements were compared to neat BPs prepared by the authors. Similar results were found by Pham et al [58] in a study of BP/polycarbonate composites, since the Young modulus and tensile strength increased by about 120 and 200%, respectively. Also, the mechanical properties of BP/polymer composites can be highly influenced by the processing technique employed during the consolidation of the material.…”
Section: Properties Of Bp/polymer Compositessupporting
confidence: 89%
“…Consequently, this material is used in diverse applications such as artificial muscles [53] , electrodes [54] , field-emission [55] , fire shields [56] , and for water purification [57] . Also, BPs can be used to prepare polymer composites with uniform tube dispersion, controlled nanostructure and high CNT loading (up to 60 wt%) [58] .…”
Section: Cnt Buckypaper Reinforced Polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation